6x-10x+20=-2x+6

Simple and best practice solution for 6x-10x+20=-2x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-10x+20=-2x+6 equation:


Simplifying
6x + -10x + 20 = -2x + 6

Reorder the terms:
20 + 6x + -10x = -2x + 6

Combine like terms: 6x + -10x = -4x
20 + -4x = -2x + 6

Reorder the terms:
20 + -4x = 6 + -2x

Solving
20 + -4x = 6 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
20 + -4x + 2x = 6 + -2x + 2x

Combine like terms: -4x + 2x = -2x
20 + -2x = 6 + -2x + 2x

Combine like terms: -2x + 2x = 0
20 + -2x = 6 + 0
20 + -2x = 6

Add '-20' to each side of the equation.
20 + -20 + -2x = 6 + -20

Combine like terms: 20 + -20 = 0
0 + -2x = 6 + -20
-2x = 6 + -20

Combine like terms: 6 + -20 = -14
-2x = -14

Divide each side by '-2'.
x = 7

Simplifying
x = 7

See similar equations:

| 6u-19=3u-4 | | 6k=4k-4 | | 5c-8=17 | | 5u+6=16u-3u+54 | | 4x+x=11 | | n^2+10n+1=0 | | 4y+x=11 | | 1h+8=-6 | | -6w-12=9(w+7) | | p^2-4p-60=0 | | 5x+9x+26=180 | | -5(3b+4)+(16b-9)=0 | | 5x+9x+20=180 | | 5(4x-2)=-10 | | 5r^2+11r+6=0 | | 0.5x=0.3+9 | | 3m^2+40+100=0 | | -3y+7=-9y+49 | | 4x-4=13x-54 | | 10p+3p^2=-3 | | x-6two-thirds=3one-third | | 3x+28=8x+13 | | x-6.66=3.33 | | 69+2x=85+2x | | x(x-3)(x-2)=0 | | 69+7x=85+7x | | 0.2(25-5a)=4-a | | 4x-3+6x+8=90 | | 2m^2+4m^2+m+2=0 | | 2m^2+1+4m^2+m+2=0 | | 2m^21+4m^2+m+2=0 | | x=y+5.00 |

Equations solver categories